Penggunaan Media Flashcard Dalam Mengembangkan Bahasa Ekpresif Anak Usia 4-5 Tahun - Zaenudin, Irfan Muhammad; Mudilah, Ulfah Nurul (Jurnal Riset Manajemen Indonesia, 2020)
The background of this research problem is that there is still a lack of mastery of children's vocabulary. The purpose of this study was to find out how the teacher's efforts in planning, implementing teacher learning and evaluating the use of flashcard media in early childhood in PAUD Ar-Rafiq, Mekarraya Village, Garut Regency. This research is a descriptive qualitative research involving teachers in group A, data is collected through observation, interviews, and document analysis, data is analyzed qualitatively by using data reduction, data display, and drawing conclusions. The results showed that the teacher's efforts in using flashcard media to develop the expressive language skills of group A children were as follows, First, the teacher prepared a learning plan using flashcard media according to the theme and purpose, namely by making Weekly Learning Program Plans (RPPM) and Daily Learning Program Plans (RPPH) and teachers prepare learning media. Second, the teacher carries out learning activities using a scientific approach with 2 M indicators, among others and observing. Third, the teacher evaluates learning activities in the form of checklists, anecdotal notes, and assessment of the work. These three activity steps have been implemented by teachers at PAUD Ar-Rafiq, Mekarraya village, Garut district and can be an alternative for developing cognitive abilities of early childhood.